An approach to product development with scenario planning: The case of aircraft design. (August 2015) - Randt, Niclas P.
Highlights: Scenario planning techniques are used to find robust design requirements. A case study in aircraft design is depicted. Futures scenarios support customer orientation in product development. Scenario planning helps handling uncertainty about customer requirements. Abstract: Any product development process must start with a thorough analysis of the customer needs that the product is aimed at satisfying. This, however, is a challenging task, as customer needs tend to vary over time. As future is uncertain, a significant degree of uncertainty is attached to the anticipation of the future customer needs. This issue is especially relevant to manufacturers of aircraft, as extensive development costs and long product life cycles require a solid decision basis when initiating a new aircraft development program. Therefore, this paper is targeted at supporting the anticipation of future customer needs under uncertainty by proposing an approach to the derivation of robust design requirements through the consideration of alternative future scenarios. The approach is composed of several methodical steps that comprise the building of multiple scenarios, a scenario-specific analysis of the target market and customers, a description of distinct Concepts of Operations, and eventually a derivation of design requirements to form the aircraft specification. The paper ultimately portrays a case study that demonstrates the applicability and allows further evaluation of the proposed approach.